Association of inflammatory cytokines with type 2 diabetes mellitus and diabetic nephropathy: a bidirectional Mendelian randomization study - Song, Siyuan; Ni, Jing; Sun, Yuqing; Pu, Qiang; Zhang, Li; Yan, Qianhua; Yu, Jiangyi (Frontiers in Medicine, 2024)
Previous observational studies have suggested associations between various inflammatory cytokines with type 2 diabetes mellitus and diabetic nephropathy. However, the causal association remains uncertain.